INOVASI PENGOLAHAN PRODUK UNTUK MEWUJUDKAN KETAHANAN PANGAN DI MASA PANDEMI COVID 19 - R. Neneng Rina Andriani; Tedi Rustendi; Rina Marliana; Wildan Dwi Dermawan (Universitas Pendidikan Indonesia, 2022)
The rapid development of technology has become an opportunity as well as providing solutions for the people who created the corona virus (COVID-19) pandemic. The problems that occurred due to the pandemic resulted in the weakness of people's purchasing power coupled with the termination of employment, through the PbM-KP program we intend to educate the community to be able to meet their own needs, namely through product processing innovations to realize food security during the Covid 19 pandemic. The problem raised is the lack of competence and innovation in Cicurug Village, Pamegatan Hamlet, Margahayu Village, Manonjaya District, Tasikmalaya Regency in managing its resources. Cicurug Village, Pamegatan Hamlet, Margahayu Village, Manonjaya District, Tasikmalaya Regency has great potential in improving community welfare if it gets training and knowledge, one of which is in terms of product processing innovations that can be marketed with a wider range. Therefore, training and providing additional equipment for product processing innovations is expected to strengthen public understanding and knowledge in an effort to realize food security during the COVID 19 pandemic.